Critical language assessment literacy of EFL teachers: Scale construction and validation. (October 2022) - Tajeddin, Zia; Khatib, Mohammad; Mahdavi, Mohsen
Critical language assessment (CLA) has been addressed in numerous studies. However, the majority of the studies have overlooked the need for a practical framework to measure the CLA dimension of teachers' language assessment literacy (LAL). This gap prompted us to develop and validate a critical language assessment literacy (CLAL) scale to further underscore the role of CLA principles and their practice as an essential part of teachers' LAL. In the first phase, a pool of items was generated through a comprehensive review of the related studies. In the quantitative phase, the developed scale was administered to 255 English as a foreign language teachers selected through convenience and snowball sampling. The data were analyzed through exploratory factor analysis for construct validity and Cronbach's alpha for estimating internal consistency. The results showed that the items loaded on five factors: (a) teachers' knowledge of assessment objectives, scopes, and types; (b) assessment use consequences; (c) fairness; (d) assessment policies; and (e) national policy and ideology. It was found that the scale had a high level of internal consistency and construct validity, which suggests that this scale has the potential to be useful in assessing language teachers' CLAL and to raise language teachers' awareness of CLAL constructs.